Sociological Analysis of Pre-marital Intercourse Activities (Zina) (Criticism of Legal Interpretation Surah An-Nur Verse 3 Tafsir Al-Misbah) - Armi, Mhd. Ilham; Azwar, Zainal; Fitri, Annisa; Puspita, Mega (Transformatif, 2024)
Adultery and marriage are discussed concerning ideality. Marrying an adulterer becomes a legal issue that needs to be studied due to the impropriety of marrying an adulterer. This study analyzes the effect of adultery on future marriages in interpreting Al-Misbah surah An-Nur verse 3, written originally by M. Quraish Shihab. In addition, the interpretation by Quraish will also be parsed with Rebbeca F. Plante's sociology of sexuality analysis to connect the context study of an adulterer's marriage described in Tafsir Al-Misbah with the stigma of sexuality that occurs due to the act of penetration before marriage. The method used is qualitative with a normative-juridical approach, and to sharpen and deepen this study, a sociological analysis of sexuality is used. This study explains that Tafsir Al-Misbah interprets verse 3 of Surah An-Nur with circumstances that benefit one gender and harm the female to achieve the ideal of marriage. With a social approach, there is an implicit stigmatization effort in the interpretation of verse 3 of Surah An-Nur by labeling adulterous females as partners who are not ideal for marriage. This also indicates that socially, a female with such stigmatization is presented as having a bad sexual reputation and provides space for injustice for a female to choose a partner with ideal considerations as befits a male who desires a partner with ideality towards marriage. Thus, the interpretation of the law in verse 3 of surah An-Nur in Tafsir Al-Misbah appears to disadvantage one gender (female) subjectively.